Chinese Tofu‐Inspired Biomimetic Conductive and Transparent Fibers for Biomedical Applications. Issue 4 (26th February 2023) - Chen, Shuo; Jiang, Sihan; Qiao, Dan; Wang, Jiangyue; Zhou, Qiangqiang; Wu, Chunmao; Li, Xuefei; Neisiany, Rasoul Esmaeely; Sun, Lijie; Liu, Yuehua; You, Zhengwei; Zhu, Meifang; et al.
Abstract: Conductive fibers are vital for next‐generation wearable and implantable electronics. However, the mismatch of mechanical, electrical, and biological properties between existing conductive fibers and human tissues significantly retards their further development. Here, the concept of neuro‐like fibers to meet these aforementioned requirements is proposed. A new wet spinning process is established to continuously produce pure gelatin hydrogel fibers. The key is the controllable and rapid gelation of spinning solutions based on the salting‐out effect, which is inspired by the Chinese food tofu. The resultant fibers exhibit neuro‐like features of soft‐while‐strong mechanical properties, high ionic conductivity, and superior biological properties including biodegradability, biocompatibility, and edibility, which are crucial for implanted applications but seldom reported. Furthermore, all‐weather suitable neuro‐like fibers with excellent anti‐freezing and water retention properties are developed by introducing glycerol for wearable applications. The optical fiber, transient electronics, and electronic data glove made of neuro‐like fibers profoundly demonstrate their potential in biomedical applications. Abstract : A continuous and controllable strategy of protein‐based hydrogel fibers by wet spinning of gelatin solutions based on the Hofmeister effect is developed. The neuro‐like fibers of gelatin simulating the mechanical, biological, and electrical properties of nerve tissues represent a new concept of conductive fibers and a series of highly desired features for bio‐integrated electronics.